2019
DOI: 10.1111/1365-2664.13391
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and community consequences of captive propagation in mosquitofish

Abstract: Captive propagation can lead to phenotypic change in fish populations, but the broader community‐level consequences of captive phenotypes remain largely unknown. We investigate the degree to which captive propagation alters the phenotypes and ecological roles of fish stocked into wild communities. We focus on captive propagation of western mosquitofish (Gambusia affinis) for biocontrol, which represents one of the largest scale production efforts for any fish released into the wild. Captive propagation in mosq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…Where populations coexist, mosquitofish express traits that increase their survival in the presence of bass (i.e. adaptations), such as increased vigilance and streamlined body shapes that increase escape ability [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Where populations coexist, mosquitofish express traits that increase their survival in the presence of bass (i.e. adaptations), such as increased vigilance and streamlined body shapes that increase escape ability [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…We also collected fish from two additional wild ponds and MVC 'pond' sources in central California in May 2017. The MVC sources are from two mosquitofish captive propagation facilities in central California, which breed mosquitofish completely in captivity for several generations with limited wild genetic input, resulting in some evidence of domestication [47]. We transported the fish to the University of Maine mosquitofish breeding facility after roughly one week of holding in Santa Cruz, CA.…”
Section: Methods (A) Fish Sourcesmentioning
confidence: 99%
“…We measured growth and survival of mosquitofish in mesocosms with largemouth bass predators (Macropterus salmoides) absent or present, respectively. Poeciliid fishes-like mosquitofishhave been model taxa for evolutionary ecology, showing strong phenotypic responses to predator introductions and removals [32][33][34]43,44], as well as strong ecological impacts of phenotypic change [2,6,8,[45][46][47][48]. We test two sets of competing Drosophila melanogaster immunological defenses against parasitoids are associated with slower feeding [13] morphological Gambusia affinis mosquitofish have body forms hydrodynamically optimized for either efficient feeding or fast escape [14] Rana sylvatica head and body morphologies that enhance predator escape reduce feeding and digestive efficiency [15,16] life-historical Poecilia reticulata earlier maturation to avoid predation results in decreased reproductive output [17] Rana lessonae reduced activity and growth in the face of predators increases the risk of desiccation in temporary pool environments [18] behavioural Melanoplus femurrubrum hiding increases survival but decreases feeding rate [19] Poecile atricapillus travelling with food items to cover reduces predation risk but also reduces feeding efficiency [20] royalsocietypublishing.org/journal/rspb Proc.…”
Section: Introductionmentioning
confidence: 99%
“…These strong trophic effects potentially make mosquitofish useful in tying ongoing or recent trait changes to ongoing or recent ecosystem changes, as is the goal in the burgeoning field of eco‐evolutionary dynamics (Hendry, 2016). Intraspecific variation among mosquitofish populations has been shown to have substantial ecosystem consequences (Fryxell & Palkovacs, 2017 WM; Wood et al., 2019 WM, Wood et al, 2020a, 2020b WM; Fryxell, Wood, et al., 2019 WM), although the relative contribution of evolution versus plasticity to these effects merits future investigation.…”
Section: Mosquitofish As a Model Systemmentioning
confidence: 99%
“…The study of mosquitofish traits after their introduction into novel conditions has consistently demonstrated their capacity for rapid trait changes. By comparing invasive populations that share recent common ancestors, studies have shown significant among‐population variation in traits like environmental tolerance (Vinson et al., 1963; Meffe et al., 1995 EM; Stockwell & Vinyard, 2000 WM; Annabi et al., 2009 WM), life history (Kahn et al., 2013; Stearns, 1983a EM), metabolism (Moffett et al., 2018 WM), antipredator traits (Fryxell et al., 2019 WM) and morphology and behaviour (Ouyang et al., 2018 WM; Wood et al., 2019 WM). In some cases, this interpopulation trait variation has been shown to have a genetic basis (Stearns, 1983b; Meffe et al., 1995 EM; Stockwell & Weeks, 1999 WM; Fryxell et al., 2020 WM), highlighting the speed of evolutionary changes that may commonly occur in nature (Hairston et al., 2005; Hendry et al., 2008).…”
Section: Mosquitofish As a Model Systemmentioning
confidence: 99%